Palatability and hygiene characteristics of dry‐aged pork and optimisation of dry ageing period. (22nd January 2020) - Nam, Oh Seong; Park, Inmyoung
Summary: To improve upon understanding of the quality characteristics of dry‐aged pork, pork belly and arm shoulder were dry‐aged for 0, 7, 14, 21 and 28 days. Their physicochemical, free amino acid (FAA) content and microbiological analysis were performed to evaluate palatability and hygiene. After 28 days of ageing, total FAA content increased by 56.1% and 71.4% for pork belly and arm shoulder, respectively. The amount of individual FAAs increased, except for glutamine. At 28 days, total bacteria and coliform continuously increased to 4.40 and 4.43 log (CFU g −1 ) for pork belly sample, respectively, and 5.92 and 4.26 log (CFU g −1 ) for arm shoulder sample, respectively; moreover, E. coli was first detected and Salmonella spp. and Listeria spp., which are considered indicators of meat food poisoning, were not detected. Altogether, extended dry ageing period can impose a potential hygiene concern, though palatability is increased, requiring optimisation in the dry ageing process. Abstract : Free amino acid and microbial analysis of dry‐aged pork during 0, 7, 14, 21 and 28 days of dry ageing periods.